The food safety culture in a large South African food service complex: Perspectives on a case study - Griffith, Christopher J.; Jackson, Linda M.; Lues, Ryk (Emerald Publishing: British Food Journal, 2017)
The purpose of this paper is to assess elements of food safety management and food safety culture within a prominent South African entertainment, hotel and food service complex. Design/methodology/approach In this paper a qualitative case study approach was used. Following a comprehensive literature review, based on factors known to be important in developing a food safety culture, in combination with national and international food safety standards, an interview guide was constructed and utilised in a series of semi-structured interviews. The interviewees represented different management levels involved in food delivery but did not include board level managers. Findings Many of the factors considered important in good food safety management, including the presence of a formal food safety policy and the creation and maintenance of a positive food safety culture, were absent. Although a formal system of internal hygiene auditing existed and food safety training was provided to food handlers they were not integrated into a comprehensive approach to food safety management. Food safety leadership, communication and support were considered deficient with little motivation for staff to practise good hygiene. Originality/value Food safety culture is increasingly recognised as a contributory factor in foodborne disease outbreaks and is the focus of increasing research. However, although every food business has a unique food safety culture there are relatively few published papers concerning its analysis, application and use within specific businesses. This case study has identified food safety culture shortcomings within a large food service facility suggesting there was a potentially significant food safety risk and indicates ways in which food safety could be improved and the risk reduced. The results also suggest further work is needed in the subject of food safety culture and its potential for reducing foodborne disease.
Published Article
Keywords: South Africa; Food hygiene training; Food safety culture; Food safety management; Management commitment